Performance in the 1.2 km shuttle run test reflects fitness capacities in rugby players. - Sella, F. S.; Hébert-Losier, K.; Beaven, C. M.; McMaster, D. T.; Harvey, M.; Gill, N. D. (Journal of Australian Strength and Conditioning, 2021)
The relationships between performance in the 1.2 km shuttle test (Bronco) with the Multistage Shuttle Run Test (MSRT) and Yo-Yo Intermittent Recovery Test Level 1 (Yo-Yo IR1) in rugby players were investigated. Additionally, differences in Bronco, MSRT, and Yo-Yo IR1 scores between backs (B) and forwards (F), and rugby codes were assessed. Data from professional players (23 rugby sevens and 133 rugby union) were analysed. All rugby sevens players performed the Bronco and MSRT, whereas rugby union players completed the Bronco and Yo-Yo IR1. The relationship between the Bronco and MSRT or Yo-Yo IR1 was quantified using Pearson`s r, whereas differences between playing positions and codes were quantified using Hedges` g effect sizes (ES). Large correlations were observed between Bronco and MSRT (r = -0.57 and 0.53). Very large correlations were observed between Bronco and Yo-Yo IR1 (r = -0.74 and 0.71). Similar Bronco (B: 289 ± 10 s; F: 291 ± 10 s) and MSRT (B: 2470 ± 162 m; F: 2446 ± 236 m) scores were found in rugby sevens backs and forwards, while moderately better Bronco (B: 294 ± 15 s; F: 311 ± 21 s) and Yo-Yo IR1 (B: 1985 ± 367 m; F: 1627 ± 375 m) scores characterised rugby union backs (ES = -0.90 and 0.96). Small to moderately better Bronco scores were observed in rugby sevens compared to rugby union players (ES = -0.36 to -0.99). These results support the utility of the Bronco as a fitness test in rugby. The low shared variance observed between the Bronco and the two other tests, however, indicates the scores derived from these tests (e.g., speed) are not interchangeable.